Prevalence of Eclampsia and Its Maternal-Fetal Outcomes at Gandhi Memorial Hospital, Addis Ababa Ethiopia, 2019: Retrospective Study - Wassie AY; Anmut W (Dove Medical Press, 2021)
Addisu Yeshambel Wassie, Walellign Anmut Department of Midwifery, College of Health Science and Medicine, Wolaita Sodo University, Wolaita Sodo, EthiopiaCorrespondence: Addisu Yeshambel Wassie Email addisyes3@gmail.comBackground: Eclamptic disorder during pregnancy is one of the common problems in sub-Saharan countries and forms one of the deadly triads along with hemorrhage and infection which complicates feto-maternal outcomes of pregnancy. So, the purpose of this study was to assess the prevalence of eclampsia and its maternal and fetal outcome in Gandhi Memorial Hospital, Addis Ababa Ethiopia, 2019.Methods: A descriptive retrospective cross-sectional study was employed on a review of all cases of women who were delivered at Gandhi memorial Hospital from 1st of September 2017 to –last of August 2018. Data were analyzed using SPSS version 25 software. Descriptive statistics were used to calculate frequencies and percentages and data was presented using texts and, tables.Results: Out of the total deliveries, the prevalence of eclampsia was found to be 6.2%. In our experience of a very high rate of eclampsia, fortunately, we had only 3 maternal deaths out of the total cases. However, neonatal mortality and stillbirths had been extremely high: 41 (22.1%) of stillbirths and 30.3% neonatal deaths (a total burden of 52.4% of perinatal mortality). About 70.8% had reported a history of prior pregnancy-induced hypertension and 73.5% induced their current pregnancy following eclampsia. From mothers who required interventions to terminate the pregnancy by induction, 47.8% ended by cesarean section secondary to non-reassuring fetal status (29.2%). The majority (91.9%) had taken magnesium sulfate for the management of convulsion and 86.5% had taken hydralazine for hypertension management. Abruption of the placenta (96.2%), postpartum-hemorrhage (89.2%), and HELLP syndrome (83.8%) were major maternal adverse outcomes reported, and 22.1% of pregnancy was ended as stillbirth. Over 53.6% of delivered babies, 18.4% of neonates required admission to nursery/NICU referral.Conclusion: The prevalence of eclampsia was relatively high, with corresponding high maternal and perinatal morbidity and mortality. Increasing early detection before pregnancy, antenatal screening, and the use of magnesium sulfate to control convulsions will reduce the disorder and associated morbidity and mortality for both mother and fetus.Keywords: eclampsia, prevalence, feto-maternal outcome, Ethiopia